KISAH PUTERI CINDERELLA DAN 18 DONGENG TERKENAL LAINNYA: MENGGALI POTENSI ANAK MELALUI BUKU BACAAN (KISAH PUTERI CINDERELLA DAN 18 DONGENG TERKENAL LAINNYA: EXPLORING THE POTENTIAL OF CHILDREN THROUGH READING BOOKS) - Derri Ris Riana (Kadera Bahasa, 2018)
43Children’s reading books originating from folklore are very important in transmitting local wisdom and values to children. However, not all folklore is suitable for consumption by children. The book Kisah Puteri Cinderella dan 18 Dongeng Terkenal Lainnya is a children’s reading originating from folklore, but has been adapted for children’s readers, both in terms of content and language. The problem raised in this study is how to present stories, what themes appear, and what potential can be explored in the book Kisah Puteri Cinderella dan 18 Dongeng Terkenal Lainnya By using descriptive analysis method and narrative theory of children’s stories, this study aims to explain the presentation of the story in the book Kisah Puteri Cinderella dan 18 Dongeng Terkenal Lainnya so that it is worthy of being used as children’s reading material, describing themes that usually appear in children’s stories, and reveal the potential of children who can be explored after reading children’s stories. The results of the analysis show that the presentation of the story in the book Kisah Puteri Cinderella dan 18 Dongeng Terkenal Lainnya. it is appropriate for the readers of children, both in terms of content, language and illustrations. The themes that emerge are diverse, including cruel stepmother, someone who has extraordinary abilities, friendship between humans and other living things, and love between mother and child. Meanwhile, the potential of children that can be extracted from the story of the child is imagination, social, spiritual, and intellectual potential